PENGEMBANGAN KETERAMPILAN KEPEMIMPINAN - Bakhtiar, Bakhtiar (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
Leaders who carry out their leadership to make the institutions they lead more successful and advanced must master and develop various leadership skills, especially interpersonal skills, trust-building skills, and decision-making skills. The results of the research analysis show interpersonal skills as skills to be able to understand and communicate with others, see differences in expression, empathy, encouragement, concern, help, support, benevolence, sensitivity, skills, temperament, motivation and ability to form and maintain relationships and know various roles contained in an institution, both as a member and leader of the group. Meanwhile, skills build trust by increasing communication, commitment, information sharing, and loyalty among team members and within institutions/institutions. Then decision-making skills by identifying problems, filtering various information, identifying decision criteria, formulating weights on each decision criteria, developing decision alternatives, analyze decision alternatives, choose decision alternatives, implement decision alternatives, and evaluate decision alternatives.